Reconstruction of the evolution of the vegetation cover and the frequency of forest fires of the Sebezh Poozerie - Kupriyanov, Dmitry A.; Pisarchuk, Natalia M.; Shatunov, Anton E.; Borodina Ksenia А. (Journal of the Belarusian State University. Geography and Geology, 2023)
The results of the study of sediments of the new section of the Shkredy Bog in the key area within the National Park «Sebezhsky» are presented. This key area represents typical geosystems for the Sebezh Poozerie. The evolution of the vegetation cover and the frequency of forest fires in the Sebezh Poozerie, as well as the factors that caused changes in the vegetation cover and fire regimes within the key area, were reconstructed. Similar studies have not been conducted for the studied area before. The reconstruction is based on the data of analysing the physico-chemical properties of bog sediments (loss on ignition and humification analysis, spore-pollen and anthracological analysis, botanical analysis of peat). The relatively small size of the bog chosen for the study is due to the indicator ability of small bogs to reflect local changes in vegetation cover due to the accumulation of pollen and macroscopic charcoal particles from the territory with a radius of 1.5–2.5 km from the edge of the bog. Based on the changes in the composition of the pollen spectra, eight pollen zones were identified, united into three phases of vegetation development. This phases are correlated with the results of the analysis of macrocharcoal particles, loss on ignition, optical density, and are also supported by cluster analysis. The identified phases of vegetation cover evolution are correlated with changes in forest fire activity. Phase I is characterised by the predominance of coniferous-broadleaf forests with significant birch participation and frequent forest fires caused primarily by warm and dry climatic conditions. Phase II is characterised by the spread of coniferous-broadleaf forests with significant participation of thermophilic species with minimal the impact of the pyrogenic factor in a wetter climate. Phase III is characterised by the dominance of birch-pine forests and the active development of waterlogging processes with the significant participation of forest fires. The transformation of vegetation cover in phase III is caused by both climatic causes and anthropogenic impact, and forest fires had a mixed genesis in the conditions of the beginning of the active transformation of the natural environment by human impact.